Restrição no balanço de pagamentos e crescimento econômico no Brasil: considerações sobre o padrão de especialização da estrutura produtiva - Frugis, Paulo Roberto Ribeiro (2015)
This thesis aims to evaluate empirically the applicability of Thirlwall's Law for the Brazilian economy in the period from 1948 to 2013 whereas the specification proposed by Carvalho and Lima (2009) that includes individually all the components of the payments balance: international trade, terms of trade, capital flows (considered without limits the entry) and interest payments. In doing so it shows the contribution of each of these components to the aggregate growth of the product. The specification of Carvalho and Lima (2009) will be test for the period 1948-2004 and faced with the application developed by the authors for the periods 1930-2004 and 1994-2004. Since the model allows to identifying the contribution of each component of the payments balance for income growth, this analysis aims to evaluate its evolution in the past twenty years. The individual behavior of these parameters will allow work to discuss aspects of international trade in Brazil and specialization of its productive structure in the period. It is possible to observe an ongoing process of continuous worsening of reason of income-elasticities export/import that imposes greater restrictions on economic growth given by structural imbalances in the balance of payments